2003
DOI: 10.1021/ma034440x
|View full text |Cite
|
Sign up to set email alerts
|

Design of Mechanically Robust High-Tg Polymers:  Synthesis and Dynamic Mechanical Relaxation Behavior of Glassy Poly(ester carbonate)s with Cyclohexylene Rings in the Backbone

Abstract: High-T g yet mechanically robust polymers are desirable but difficult to realize. To explore whether the insertion of a motionally active molecular entity in the backbone could produce polymers with both high T g and yet are not brittle, three series of high-T g glassy polycarbonates/polyesters/poly(ester carbonate)s were designed and synthesized. The secondary relaxation behavior of these polymers was studied by dynamical mechanical analysis (DMA). Incorporation of cyclohexylene groups (C-rings) in the main c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 35 publications
2
34
0
Order By: Relevance
“…Most of them are engineering thermoplastics based on poly(phenyl esters) or poly(phenyl ketone), such as poly(2,6‐dimethyl‐1,4‐phenylene oxide) (PPO) ( l p ≈ 1.3 nm, T g = 211 °C), poly(bisphenol carbonate) ( l p ≈ 1.7 nm, T g = 150 °C), and so on. [1a,14] Graft polymer with semiflexible backbones may not only obtain the higher toughness over polymers with flexible backbones, but also could overcome the processing and synthetic problems in semirigid graft polymers. It is necessary to investigate such architectural advantages to design new thermoplastics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of them are engineering thermoplastics based on poly(phenyl esters) or poly(phenyl ketone), such as poly(2,6‐dimethyl‐1,4‐phenylene oxide) (PPO) ( l p ≈ 1.3 nm, T g = 211 °C), poly(bisphenol carbonate) ( l p ≈ 1.7 nm, T g = 150 °C), and so on. [1a,14] Graft polymer with semiflexible backbones may not only obtain the higher toughness over polymers with flexible backbones, but also could overcome the processing and synthetic problems in semirigid graft polymers. It is necessary to investigate such architectural advantages to design new thermoplastics.…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to investigate such architectural advantages to design new thermoplastics. Compared with semirigid polymers,[6d,15] these semiflexible polymers usually have lower T g , which are easier for processing in melt and solution,[14a,16] thus more convenient to prepare graft polymers.…”
Section: Introductionmentioning
confidence: 99%
“…The calculated T g of PAI‐1 is 18 K higher than PAI‐4 as compared with an increase in 22 K observed in DMA studies. It is generally accepted that T g of an amorphous polymer is determined by α relaxation or segmental motion of the chains, which in turn is affected by the free volume and/or rigidity of the chains. The availability of more free volume and less chain rigidity leads to faster relaxation resulting in lower T g and vice versa.…”
Section: Resultsmentioning
confidence: 99%
“…To analyze the segmental relaxation, dihedral autocorrelation function C ( t ) was calculated as follows: Ctrue(ttrue)= cos[α(t)α(t+Δt)]t where α ( t ) and α ( t + Δ t ) denote the torsional angle at time t and time t + Δ t , respectively. The time‐scale of decay of C ( t ) gives a measure of the rigidity of chains, where a longer time‐scale would signify increased rigidity . The comparison of C ( t ) for both PAI‐4 and PAI‐1 is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…In this work, in order to improve the toughness and compensate for the low reactivity of OPD, while at the same time retaining the rigidity of OPD-based PCs, BHEEB is incorporated in the polymer chains by melt polymerization with OPD in different molar ratios. Previous investigations suggested that the high impact strength of BPA-PC can be attributed to its capacity of absorbing high impact energy which, in turn, has been correlated with secondary relaxations involving cooperative motions of BPA units in the polymer chains . It is worthy to note that although BPA is toxic, however, BHEEB is biocompatible.…”
Section: Introductionmentioning
confidence: 99%